2008
DOI: 10.1055/s-2008-1070828
|View full text |Cite
|
Sign up to set email alerts
|

Das Amyloid der Langerhansschen Inseln und seine Beziehung zum Diabetes mellitus* 1

Abstract: After grading into 4 groups of severity the extent of amyloidosis of the islets of Langerhans was investigated in 60 patients with diabetes and in 60 without. Distinction of 3 stages of diabetes according to clinical parameters showed clear connections between the stage of diabetes and the extent of amyloidosis. Development of amyloid locally may be evidence for progressive B cell insufficiency in diabetes of adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Amyloid deposition in T2D islets is localized to the perivascular space (de Koning et al 1994;Narita et al 1992;Schneider et al 1980) and is associated with increased β cell apoptosis and β cell loss (Jurgens et al 2011). In this study, islet amyloid was present in 8/9 diabetic subjects (comprising, on average, 14% ± 4% of islet area).…”
Section: Association Between Fragmentation Of Islet Capillaries and Amentioning
confidence: 53%
See 1 more Smart Citation
“…Amyloid deposition in T2D islets is localized to the perivascular space (de Koning et al 1994;Narita et al 1992;Schneider et al 1980) and is associated with increased β cell apoptosis and β cell loss (Jurgens et al 2011). In this study, islet amyloid was present in 8/9 diabetic subjects (comprising, on average, 14% ± 4% of islet area).…”
Section: Association Between Fragmentation Of Islet Capillaries and Amentioning
confidence: 53%
“…This is due to both functional abnormalities in the β cell, which manifests as impaired insulin release (Porte 1991), and decreased β cell mass (Butler et al 2003;Jurgens et al 2011;Klöppel et al 1985;Rahier et al 2008). Islet amyloid, similar to collagen deposition (Hayden et al 2008), is found in the extracellular matrix that lies between β cells and islet capillaries (de Koning et al 1994;Narita et al 1992;Schneider et al 1980,). However, our understanding of the mechanisms of β cell loss and dysfunction in diabetes remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that these insoluble mature hIAPP amyloid deposits cause pancreatic beta-cell loss since amyloid deposits were found in the majority of individuals with type 2 diabetes [32–34]. Furthermore the extent of extracellular amyloid deposition correlated with beta-cell apoptosis and beta-cell loss [35] as well as clinical severity of the diabetes [36]. However, several recent studies suggested that it is soluble hIAPP oligomers rather than insoluble amyloid deposits that represent the main cytotoxic species [2, 3741].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that overexpression of IAPP contributes to pancreatic amyloid formation and development of T2DM, this viewpoint supported by transgenic mouse and rat studies involving the overexpression of human IAPP (hIAPP) in islets of Langerhans [ 5 ]. Clinical studies indicate that hIAPP preferentially forms the amyloid deposition that implicates the pathology of islet hyalinization which is the pathological characteristic of T2DM [ 6 – 8 ]. Amyloid deposition is observed not only in patients with T2DM but also in some overweight or non-diabetic individuals [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%